Constructing meaning and emotional intimacy through deixis in Rosé’s song lyrics - Nurjannah, Nurjannah; Sahur Saerudin (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2025)
This study investigates deixis in selected songs from Rosé’s Rosie album by identifying deictic types and analyzing their pragmatic functions. Five songs, namely Number One Girl, Toxic Till the End, Two Years, Drinks or Coffee, and APT, were intentionally chosen for their rich emotional content and contextual diversity. The research shows that deixis serves as a discourse strategy that creates emotional closeness, narrative viewpoint, and interpersonal bonds in modern song lyrics. Using a descriptive, qualitative approach with a pragmatic focus, data collection involved stages such as selecting songs, identifying deictic expressions, coding, and interpretive analysis. Results identified five types of deixis: person, spatial, temporal, social, and discourse. A total of 119 expressions were found: 68 person, 17 spatial, 19 temporal, 8 social, and seven discourse deixis. Person deixis is most prominent, indicating the singer’s personal engagement and emotional perspective as they portray love, loss, and relationships. Overall, the findings emphasize the vital role of deixis in shaping meaning, emotional depth, and interpersonal connections in song lyrics.